A potential vorticity perspective on cyclones over South America - Crespo, Natália Machado (2019)
This study presents a general overview of the atmosphere from a potential vorticity (PV) perspective at upper levels, focusing on the influence of upper-level PV anomalies and structures and their influences on surface cyclones over South America. Surface cyclones and PV structures on isentropic surfaces (PV streamers and PV cutoffs) are identified using ERA-Interim reanalysis for the period 1979-2017. After identifying cyclones in four regions (Argentina, Uruguay, SEBrazil and Andes), their traveled distance, intensity, lifetime, association with PV structures, and time lags are analyzed in different seasons. The cyclone tracking showed that i) before cyclogenesis in Uruguay there is a high frequency of cyclogenesis in Andes; ii) a bi-modal distribution of cyclones in terms of displacement, intensity and lifetime, indicating two different types of cyclones occurring in Argentina, Uruguay and SEBrazil. In general, cyclones from Argentina and Uruguay travel longer distances and are more intense. In the four regions, PV streamers occur frequently during cyclogenesis, typically located to the southwest. However, there are seasonal differences during genesis: in Argentina and Andes, PV streamers occur mainly in summer, in Uruguay in summer and winter, and in SEBrazil mainly in winter. PV streamers frequency for each region varies, e.g., in Argentina and Uruguay they are more frequent at 320 K, while in SEBrazil and Andes at 340 K in summer. PV cutoffs occur in lower frequency than PV streamers during cyclogenesis, however, they tend to intensify during the cyclone lifetime, which is more frequent in summer than in winter. Composites of dynamic fields (Eady growth rate-EGR, quasi-geostrophic omega, PV, upper and lower-level winds, sea level pressure, geopotential height and specific humidity) before, during and after cyclogenesis show important differences between winter and summer for each region. In Argentina, the environment is slightly more baroclinic (in respect with stronger EGR, omega and upper-level jet) in summer and cyclones develop beneath the equatorial upper-level jet entrance. In this season, the PV anomaly associated with PV streamers acts intensifying ascent and contributing to the surface cyclogenesis. In winter, cyclogenesis in Argentina occur beneath the polar exit sector of the jet stream, with weak PV streamer upstream. Similar patterns are observed in summer and winter in Uruguay, but with a stronger baroclinicity in winter. In SEBrazil and Andes the upper-level jet is far from the cyclogenetic region in summer. In this season, cyclones in SEBrazil have a more barotropic vertical structure, whereas in winter, the higher frequency of PV streamers and PV anomalies are more important for cyclogenesis in this region. Comparatively, Andes is the region with the lowest contribution of PV streamers and PV anomalies for surface cyclogenesis.